La chiamarono amplesso rubato (Euripide, Elena 22) - Lapini, Walter (Hyperboreus, 2021)
The hypothesis is advanced that in Hel. 19–20 Λήδαν κύκνου μορφώματ’ ὄρνιθος λαβών, / ὃς δόλιον εὐνὴν ἐξέπραξ’ ὑπ’ αἰετοῦ Euripides suggests the etymology Ἑλένη from ἑλεῖν εὐνήν, “she who was born from a stolen intercourse” (Zeus’ one with Leda).